Crisis, representation and resilience : perspectives on contemporary British theatre - Wallace, Clare, 1970-; Escoda, Clara; Monforte, Enric; Prado-Přez, Jos ̌Ramn̤ (Methuen drama engage, 2022)
"A collection of incisive investigations into the ways that 21st-century British theatre works with - and through - crisis. It pays particular attention to the way in which writers and practitioners consider the ethical and social challenges of crisis. Anchored in an interdisciplinary approach that draws from sociology, cultural theory, feminism, performance and philosophy, the book brings multi-faceted ideas into dialogue with the diverse aesthetics, practices and themes of a range of theatrical work produced in Britain since 2005. Topics discussed include: Ageing Austerity Gender Migrancy Race Aesthetics Companies discussed include: Theatre Uncut Take Back Theatre Camden Peoples People Lung Phosphoros Theatre Playwrights discussed include: Kwame Kwei-Armah Tim Crouch debbie tucker green Ella Hickson Charlene James Lucy Kirkwood Cordelia Lynn Andy Smith Jack Thorne Gloria Williams Chris Goode Building on recent publications in the area and engaging in dialogue with them, Crisis, Representation and Resilience considers how crisis is being re-thought and re-orientated through theatrical performance and the ways theatre invites us to respond to the many challenges of the contemporary times"--